I am not the parent I should be: Cross-sectional and prospective associations between parental self-discrepancies and parental burnout. Issue 4 (19th May 2022) - Roskam, Isabelle; Philippot, Pierre; Gallée, Laura; Verhofstadt, Lesley; Soenens, Bart; Goodman, Alicia; Mikolajczak, Moïra
ABSTRACT: Because research has shown systematic associations between self-discrepancies and several psychological disorders, self-discrepancy is considered as a transdiagnostic factor in psychopathology. The current research contributes to the literature by testing both cross-sectionally and longitudinally the role of self-discrepancies in parental burnout, an exhaustion disorder in the parenting domain where standards are high and prescriptions numerous. In three studies (including a prospective one; N1  = 109, N2  = 1689, N3 Third measurement time  = 553 parents), we showed that self-discrepancies are strongly associated with parental burnout, and Study 3 showed that they even predict rank-order increases in such burnout. These results have implications for research on self-discrepancies, parental burnout and psychopathology more broadly.